Criminal Law Enforcement Against Environmental Pollution Caused By Electronic Waste - Moch. Ainul Chodri; Sri Anggraini Kusuma Dewi; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The purpose of this research is to find out the elements of environmental crime due to electronic waste pollution based on legislation No. 32 of 2009 concerning the Protection and Management of the Environment and the application of environmental criminal law sanctions against perpetrators of environmental pollution due to electronic waste. This research method uses research normative, based on literature and case studies in the field related to environmental criminal law enforcement related to environmental pollution due to electronic waste. The results of research on the formulation of elements of environmental crimes due to environmental pollution of electronic waste, until now have not been specifically regulated in regulations even though the impact of electronic waste is very dangerous for the environment. Electronic waste, according to law and regulations No. 32 of 2009 concerning Environmental Protection and Management, is classified as Toxic and Hazardous Materials (B3), for the handling of electronic waste must require specific e-waste management policies and regulations.